Risk Perceptions of Antibiotic Usage and Resistance: A Cross-Sectional Survey of Poultry Farmers in Kwara State, Nigeria - Ahmad I. Al-Mustapha; Victoria O. Adetunji; Annamari Heikinheimo (Antibiotics, 2020)
Overwhelming empirical evidence has highlighted the contribution of indiscriminate antibiotic usage (ABU) in food animals to the overall burden of antibiotic resistance (ABR) in humans, thus making antibiotic use the main selective pressure driving antibiotic resistance. The social and behavioral perspective on antibiotic use and resistance in poultry is limited. Our study therefore aimed at obtaining information on antibiotic usage, awareness of ABR, and the attitude and perceptions towards prudent antibiotic usage and ABR. A cross-sectional survey using a structured questionnaire was conducted in 125 poultry farms in Kwara state in December 2019. Most farmers (69.6%, n = 87/125) were aware of ABR and had satisfactory knowledge about ABR with a mean knowledge score of 3.2 ± 1.5. Age (older farmers; OR: 1.1, 95% CI: 1.0, 1.2) and gender (male respondents, OR: 8.5, 95% CI: 3.0, 23.9; p < 0.01) were more likely to have satisfactory knowledge of ABR. Tertiary education was significantly associated with ABR awareness (OR: 4.7; 95% CI: 0.1, 0.7; p = 0.007) and the ABR knowledge level (OR: 7.8; 95% CI: 3.3, 18.7; p < 0.01). Higher flock size was significantly associated with a satisfactory knowledge of ABR (OR: 9.5; 95% CI: 3.8, 23.6; p < 0.01). Most of the poultry farmers (68%) had positive attitudes towards prudent antibiotic use with a mean score of 2.7 ± 0.9. On the contrary, only 32.8% of poultry farmers had a desirable perception of ABR with a mean perception score of 4.9 ± 1.1. The ABR knowledge level was significantly associated with the perceptions of farmers (p < 0.05) but not their attitudes toward ABU and ABR (p = 0.083). There was evidence of unprescribed use of antibiotics in poultry and a failure to observe antibiotic withdrawal periods. These constitute a risk of exposure to unacceptable levels of drug residues from poultry products and an increased risk of ABR. Improving education and communication on antibiotic stewardship programs are crucial to prevent the looming antibiotic threat.